FASTING BLOOD SUGAR (FBS) IN THE FIRST TRIMESTER: PREDICTIVE VALUE FOR GESTATIONAL DIABETES MELLITUS AND IMPACT ON PREGNANCY-RELATED OUTCOMES - MARYAM , B; YASMEEN , H; MANAF , A; ASIF , M; ALAM , F; ALAM , S; SOHAIL , A; HUSSAIN , Z; KHAN , M; MUSTAFA , A; AHMED , I (Biological and Clinical Sciences Research Journal, 2024)
Gestational diabetes mellitus (GDM) is a significant health concern in pregnancy, affecting maternal and neonatal outcomes. Early detection of GDM through fasting blood glucose (FBS) screening may help in timely management to prevent complications. Objective: To determine the fasting blood glucose threshold that accurately predicts the onset of gestational diabetes mellitus (GDM) and its impact on pregnancy outcomes. Methods: A prospective cohort study was conducted at the Obstetrics and Gynecology Department of Jinnah Postgraduate Medical Centre (JPMC), Karachi, from August 2023 to May 2024, involving 405 pregnant women selected through systematic random sampling. Inclusion criteria included singleton pregnancies, excluding women with pregestational diabetes or baseline fasting glucose levels of 126 mg/dL or higher. Baseline data on age, BMI, gestational age, and family history of diabetes were collected, and FBS levels were measured at the initial visit. Oral Glucose Tolerance Tests (OGTT) were conducted between 24 to 28 weeks of gestation to diagnose GDM. Maternal and fetal outcomes were monitored until delivery. Statistical analyses, including logistic regression and ROC curve analysis, were performed using IBM SPSS version 20. Results: Among the 405 participants, with a mean age of 28 ±6.49 years, the mean fasting blood sugar (FBS) was 89.5 mg/dL (±12.3). Impaired FBS (≥92 mg/dL) was noted in 24.70% of participants, and 18.27% were diagnosed with GDM following OGTT. A fasting glucose level of 127.4 mg/dL (±22.1) was observed among women diagnosed with GDM. Logistic regression showed a significant association between FBS ≥92 mg/dL and GDM risk (OR 1.08, CI 1.02-1.14, p=0.011). ROC analysis revealed an FBS cutoff of 92 mg/dL with 73% sensitivity and 68% specificity for predicting GDM. Gestational hypertension was observed in 8.64% of participants, and preeclampsia in 6.67%. Vaginal deliveries occurred in 72.1% of cases, while 27.9% required cesarean sections. Neonatal outcomes showed an 11% macrosomia rate, with 12% requiring NICU admission. Conclusion: Fasting blood glucose levels ≥92 mg/dL in early pregnancy are strongly predictive of gestational diabetes mellitus (GDM). Early FBS screening allows for timely intervention, potentially improving maternal and neonatal outcomes. This study underscores the importance of incorporating FBS screening in routine antenatal care for better pregnancy management.